Histology and Embryology for Dental Hygiene - Sheldahl, Laird; Yapp, Raye Ann (Open textbook library., 2020)
This eBook makes use of animated images to focus on concepts in histology and embryology, as well as hyperlinks to promote non-linear reading and learning. It is aimed at college students in a dental hygienist program.